(untitled) (Vietnam Journal of Community Medicine, 2022)
Glucose-6-phosphate dehydrogenase (G6PD) deficiency is the most common enzymopathy in the human population, especially those living in malaria endemic areas. Decreased G6PD enzymatic activity is associated with 8-aminoquinolines-induced hemolysis leading to severe complication, and malaria elimination challenge, especially in Plasmodium vivax malaria. This study was conducted to the enzyme G6PD activity deficiency in population are living in malaria endemic zone in Tuy Duc district, Dak Nong province. Method: In order to inform the safer use of 8-aminoquinolines, a crosssectional study which included 2,809 subjects was conducted using a quantitative CareStart™ G6PD biosensor (AccessBio, USA). Results: The results showed that the normal value of G6PD activity is 9.03 IU/g Hb, the adjusted male median is 8.78 IU/g Hb, the 30% and 80% cut-off values were 2.63 IU/g Hb and 7.02 IU/g Hb, respectively. The overall prevalence of G6PD deficiency of study population was 2,31%, with the figures for male and female were 3.65% and 1.49%, respectively. The prevalence of G6PD deficiency was significantly different among ethnic minority groups (p<0.005). Conclusions: The quantitative test should include point-of-care G6PD activity testing in clinical practice of vivax malaria to allow the safe use of 8-aminoquinolines for radical treatment.